Voluntary optimisation of antimicrobial consumption in swine and poultry production in Thailand: a policy analysis - Lekagul, Angkana; Kirivan, Supapat; Kaewkhankhaeng, Wanwisa; Khotchalai, Saowapa; Mader, Rodolphe; Tangcharoensathien, Viroj (Frontiers in Veterinary Science, 2024)
Antimicrobial resistance (AMR) is a global health concern with significant implications on economies and health security, affecting humans, animals, food, and the environment. To tackle this issue, promoting responsible antimicrobial use in livestock production has emerged as a crucial intervention. In 2018, Thailand introduced the Voluntary Optimization of Antimicrobial Consumption (VOAC) programme, with the objective to encourage responsible antimicrobial use practises. This study aimed to analyse the context, content, process and actors of the VOAC programme. A qualitative method including document reviews and key informant interviews were applied. In-depth interviews were conducted with 18 key informants who are key stakeholders from public and private sectors involved in the policy formulation, design of policy contents and implementation of VOAC: policy makers or officers responsible for animal health (n = 12), animal producers (n = 2), animal product traders or retailers (n = 2), and farm veterinarians (n = 2). Interview transcripts were validated by informants for accuracy, and triangulated with document review findings. Deductive approach was applied for data analysis and interpretation based on Walt and Gilson’s policy analysis framework. The VOAC farm certification comprises of Raised Without Antibiotics (RWA) and Reducing Antibiotic Use (RAU), both aiming to combat AMR in food animals. Global and national factors, including increased public awareness, policy commitments, export requirements from the European Union, and international organisation advocacies, influenced the development of the programme led by the Department of Livestock Development (DLD), under the Ministry of Agriculture and Cooperatives. Collaboration with the private sector facilitated policy clarity, with implementation primarily executed through regional, provincial, and district livestock officers. Integration of the programme with the pre-existing Good Agriculture Practise certification system enabled cost-effective implementation without additional resources. In 2022, DLD official data reported 214 RWA farms (112 pig and 102 broiler), and 230 RAU farms (83 pig and 147 broiler). Incentives for farms to participate in the programme include improving corporate image and demonstrating corporate responsibility addressing AMR in food products. Recommendations include optimising certification strategies, increasing consumer awareness of RWA and RAU products and strengthening monitoring and evaluation systems.